2020
DOI: 10.5014/ajot.2020.74s1-po8021
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Impact of OT Student Stress: Professor and Student Perspectives

Abstract: Date Presented 03/28/20 The purpose of this mixed-methods study was to explore how OT students and professors view student stress caused by curricular requirements. Quantitative surveys and qualitative interviews were used to gather their perspectives. Both students and professors identified moderate to high levels of student stress affecting student relationships and well-being and suggested the need for educator awareness and curricular modification for remediation of this challenging problem.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Soja et al (2016) found that the highest perceived stressors among occupational therapy students were related to their academic demands and included assignments due the same day, deadlines, projects and papers, difficulty in the upcoming week, and many tests. Non-academic stressors such as family issues, the high cost of tuition, and student loan debt continue to plague university students, including those in occupational therapy programs (Govender et al, 2015;Grab et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Soja et al (2016) found that the highest perceived stressors among occupational therapy students were related to their academic demands and included assignments due the same day, deadlines, projects and papers, difficulty in the upcoming week, and many tests. Non-academic stressors such as family issues, the high cost of tuition, and student loan debt continue to plague university students, including those in occupational therapy programs (Govender et al, 2015;Grab et al, 2020).…”
Section: Introductionmentioning
confidence: 99%